Examining the Causal Relationship between Inflation and Unemployment in Indonesia - Angga, Binanga; Aliasuddin, Aliasuddin; Abrar, Muhammad; Masbar, Raja; Saputra, Jumadil (International Journal of Business, Economics & Financial Studies, 2024)
Inflation and unemployment are significant challenges faced by both developing and developed countries. This study analyzes the causal relationship between inflation, as measured by the Gross Domestic Product (GDP) Deflator, and open unemployment in Indonesia. Using a Vector Autoregressive (VAR) panel model, the analysis is based on panel data from 34 provinces from the first semester of 2015 to the second semester of 2022. The results of statistical tests indicate a unidirectional causality, with inflation Granger-causing unemployment, but not vice versa. This finding is further supported by the Vector Autoregression estimates, where Lag 4 reveals that unemployment is primarily influenced by inflation, while inflation remains unaffected by unemployment. To address the issue of unemployment, policymakers should prioritize controlling inflation and keeping it within manageable limits, as reducing inflation could contribute to improved unemployment rates. Future research should explore the relationship between inflation and unemployment through qualitative interviews with individuals who have experienced both issues to understand their daily impacts better.